Causas que limitan la satisfacción de los visitantes de la festividad virgen de la natividad en el distrito de Tabalosos, provincia de lamas, Región San Martín- 2014 - Yessenia Anais, Melendez Romero (2016)
This research aims to determine the causes which limit the satisfaction of visitors to the Virgin Festival of Nativity Tabalosos district. Assuming that the Festival receives a considerable influx of visitors it is necessary that the Organization of the Festival, has a series of requirements that meet the needs and demands of visitors, where it involved population, tourism service providers and authorities since with the union of all actors will be performing a work that allows a pleasant experience to visitors The development of the thesis took references and data obtained in the field, research studies related to the subject, which have been embodied in the background and theoretical bases; as a result determined the research problem ¿what causes that limit the satisfaction of visitors of the Virgin Festival of Nativity of the District of Tabalosos, Lamas province, region San Martín - 2014?, also the investigation aims to determine the causes which affect the satisfaction of visitors in general, and in particular to assess the quality of service offered by restaurants and accommodation the level of tourism culture of the population, and determine if the local tourist management of the municipal authorities contribute to the better organization of the Festival Research hypothesis being low levels of quality of the services provided by the restaurants and accommodations, the weak tourist culture of the population and the poor local tourism management authorities limited the satisfaction of visitors to the Virgin Festival of the Nativity. The research method is deductive because part of a general knowledge one more particular. The infinite population formula was used for the deduction of the sample since there is a register stating the number of visitors to the Festival To complement the research applied a survey aimed at visitors, whose results show that restaurants and lodging establishments have deficiency in terms of the quality of services, workers lack of preparation at the time of the warning, they show lack of hygiene, as well as also the prices paid does not compensate to the service received. Regarding the tourist culture of the population the visitors sensed little empathy, likewise the lack of kindness and courtesy to when requesting information on the Festival or any other topic of interest. On the other hand visitors rated as deficient local tourism management because of perceived insecurity, lack of concern for environmental issues since they noticed the absence of garbage dumps as well as the lack of hygienic services enabling to satisfy the physiological needs, reason by which the visitors expressed their dissatisfaction with regard to the Organization of the Festival; to strengthen the research an interview was applied to the district mayor where stated that they currently do not have plans or projects that contribute to the Organization of the Festival the same intended economic resources are limited; Similarly, he said that the municipality does not have trained personnel in the area of tourism. Finally it is shown the respective conclusions that validated the hypothesis of investigation posed as well as also recommendations